2005
DOI: 10.3354/meps286145
|View full text |Cite
|
Sign up to set email alerts
|

Induction of larval settlement in the polychaete Hydroides elegans by extracellular polymers of benthic diatoms

Abstract: Larval settlement of the polychaete Hydroides elegans Haswell, 1883 is mediated by marine biofilms; complex agglomerates of bacteria, diatoms, fungi and protozoa enmeshed in a matrix of extracellular polymers (EPS). In our previous investigations, benthic diatoms were demonstrated to be potent mediators of larval settlement in H. elegans. The putative diatom-derived settlement cues were heat-stable components in close association with the diatom surface. For an in-depth investigation of the chemical nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 39 publications
1
38
1
1
Order By: Relevance
“…In contrast, we observed N. constricta to exhibit high growth rates at lower salinities. Similar results to ours were obtained by Lam et al (2005) and Pasztaleniec & Polec´(2006), whereas Kashima et al (1997) described N. constricta as having an optimum salinity between 25 and 56. However, different growth responses among clones of the same diatom species have been observed by different authors (e.g.…”
supporting
confidence: 91%
“…In contrast, we observed N. constricta to exhibit high growth rates at lower salinities. Similar results to ours were obtained by Lam et al (2005) and Pasztaleniec & Polec´(2006), whereas Kashima et al (1997) described N. constricta as having an optimum salinity between 25 and 56. However, different growth responses among clones of the same diatom species have been observed by different authors (e.g.…”
supporting
confidence: 91%
“…The formation of biofilm is very important for the adhesion of subsequent fouling organisms. The studies had proved that bacterial biofilm of Pseudoalteromonas spongiae was associated with its induction of larval settlement of the polychaete Hydroides elegans and the settlement was correlated with bacterial density (Lau et al, 2005;Huang et al, 2007), and the reports suggested that the extracellular polymers of benthic diatoms induced larval settlement in the polychaete Hydroides elegans (Lam et al, 2003(Lam et al, , 2005. Similarly, bacterial biofilm promoted the settlement of Ulva spores and Balanus improvisus cyprid (Joint et al, 2002;Tait and Havenhand, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The larva of H. elegans is an excellent model to study the mechanisms underlying settlement cue detection during the habitat selection process (reviewed by Qian 1999). This species is also particularly suitable for examining the relationships among environmental conditions, biofilm dynamics and larval settlement (Lam et al 2005).The role of UVR on biofilms, and consequently on the larval settlement, has as yet not been broadly investigated. In this study, we exposed sublittoral multispecies biofilms to UVR and then examined the films' ability to induce the settlement of Hydroides elegans larvae under both laboratory and field conditions.…”
mentioning
confidence: 99%